Edukasi Pemilahan Sampah untuk Meningkatkan Karakter Peduli Lingkungan Siswa SD Labschool UNEJ - Fahimatul Anis; Naomi Dias Laksita Dewi; Zetti Finali (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Waste has become a serious problem in the school environment as students are still observed disposing of trash indiscriminately. Schools, as formal institutions, can serve as a platform to instil environmental awareness in students from an early age. It is crucial to cultivate students' concern for proper waste disposal and sorting according to its type. Stemming from this issue, this community service activity aims to provide a solution through educational initiatives on organic and inorganic waste segregation. The tangible form of this community service activity involves practical education on organic and inorganic waste sorting at SD Labschool UNEJ. The method employed includes several stages: obtaining permission by processing a speaker request letter to the higher education institution, preparation by determining the schedule for the service activity, implementation in the form of educational socialization on organic and inorganic waste sorting, and evaluation by administering quizzes or questions related to waste segregation. As a result of this service activity, students have an increased level of understanding about organic and inorganic waste sorting and knowledge of waste management to enhance its functional value. In conclusion, this community service has led to an improvement in the environmental awareness character of students at SD Labschool UNEJ in sorting organic and inorganic waste.